PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. UNITED AGRO INDONESIA KAPUAS - Wahid Hasyim; Basuki Basuki (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2021)
This Studi aims to examine and analyze the influence of Organizational Culture, Organizational Commitment and the Work Environment simultaneously and simultaneously on Employee Performance at PT United Agro Indonesia. The research method uses survey methods, the type of research uses descriptive quantitative. While the nature of the research is explanatory research. Sampels were taken 86 of a total population of 630 people using the Slovin formula. Data collection was taken using interview observation techniques and questionnaires. The data analysis tool uses multiple Linier regression analysis using the IBM Statistik al version 20.The results of the t test showed that the Organizational Culture variable (X1) had a Parsial effect on the Performance of Employees at PT. United Agro Indonesia, this is evidenced by the results of the Probability or Significance value of 0,000 <0.05 with a confidence level of 95%. With these results, the First hypothesis is accepted. T test results indicate that the variable Organizational Commitment (X2) has a Parsial effect on the Performance of Employees at PT. United Agro Indonesia, this is evidenced by the results of the probability value or significance value of 0.001 <0.05 with a confidence level of 95%. T test results indicate that the Work Environment variable (X2) has a Parsial effect on the Performance of Employees at PT. United Agro Indonesia, this is evidenced by the results of the probability value or significance value of 0.007 <0.05 with a confidence level of 95%.The results of the F test analysis showed that Organizational Culture (X1), Organizational Commitment (X2) and Work Environment (X3) variables simultaneously affected Employee Performance at PT. United Agro Indonesia, This is proven by the Proportional Value or Significant Value of 0,000 <0.05 with a confidence level of 95%, then the fourth hypothesis is accepted.